Pengaruh Ekonomi Pembangunan Terhadap Sumber Daya Manusia di Indonesia - Imsar .; Restu Amelia Rambe (CV. ITTC INDONESIA, 2022)
This research is intended to determine the effect of economic development on human resources in Indonesia. by using the library research method, namely the method of collecting data by understanding and studying theories from various literatures related to the research. Based on the results of the study, it shows that economic development is very influential on human resources and it can be concluded that Indonesia is still struggling with fundamental problems in improving the quality of human resources, one of which is the ability to consume nutritious food. The cost that Indonesian people need to spend to buy a balanced nutritious meal is IDR 22,126 per day or IDR 663,791 per month. The success of achieving high economic growth is like a mirage, notreflecting the real condition of human resources. It is possible that development is only enjoyed by a handful of people, as a result the gap is widening. Similarly, economic growth is more influenced by capital (capital intensive) than by human resources (labor intensive). This can be seen from the sectors that contribute to the largest number of human resources, such as the agricultural sector, whose contribution and growth are lower than other sectors, meaning that every 1 percent of economic growth is only able to open a handful of new jobs. The success of achieving high economic growth is like a mirage, it does not yet reflect the realization of economic growth.